Performance Analysis of H-Type Darrieus Turbine Radial Projection Blades Based on NACA 0018 - Sahid, Sahid; Mulyono, Mulyono; Arif Fauzi, Dhiyaulhaq (Politeknik Negeri Semarang, 2024)
The H-type Darrieus turbine is a vertical windturbine that is used to convert wind energy into mechanicalenergy by utilizing lift force. This research is aimed at making amodified H-type Darrieus turbine blade model from a NACA0018 profile blade to a NACA 0018 blade with a chordlineprojected radially to the turbine diameter and the second resultis to compare the performance of the NACA 0018-based radialprojection blade to the performance of the NACA 0018 blade.This is preparation for searching literature, design making,manufacture of NACA 0018 blade test specimens and NACA0018 based radial shadow blades, assembly and installation oftest equipment, testing and data collection of wind turbineperformance, data processing and analysis, final results. Thevariables tested were wind speeds of 7 m/s, 8 m/s, 9 m/s, 10 m/s,11 m/s, 12 m/s. The test results show that the higher the TSR, thehigher the resulting power coefficient (Cp) until the maximumCp is reached. After that, the increasing TSR, the resulting Cp isgetting smaller. The test results show that projection bladesbased on NACA 0018 and NACA 0018 blades produce a smallmaximum Cp, respectively 0.082 and 0.124 compared to theDarrieus turbine maximum Cp reference on the vertical turbinecharacteristic chart, which is 0.4. The NACA 0018-based radialprojection produces a lower Cp than the NACA 0018 blade atspeeds of 7 m/s, 8 m/s, 10 m/s, 11 m/s, 12 m/s. At a wind speed of9 m/s the projection blade based on NACA 0018 produces ahigher power coefficient than the NACA 0018 blade. Projectingthe NACA 0018 blade chordline on the track causes the bladecross-sectional area and chordline length to shrink. The higherthe wind speed, the smaller the resulting Cp. The solidwallphenomenon affects turbine performance. Testing without loadat all wind speeds, the projection blade based on NACA 0018produces higher rotation than the NACA 0018 blade. Theparameter of the blade momentum affects the results of theturbine rotation when tested without load.